Fifth Size Strain Conference. Diffraction Analysis of the Microstructure of Materials (Zeitschrift für Kristallographie / Supplemente, 2008)
Zeitschrift für Kristallographie. Supplement Volume 27 presents the complete Proceedings of all contributions to the V Size Strain Conference in Garmisch-Partenkirchen 2007: Lattice Defects,Residual Stresses,Texture in Thin Films and at Surfaces,Line-Broadening Analysis and Line-Profile Fitting,Diffraction/Microstructure Modeling. Supplement Series of Zeitschrift für Kristallographie publishes Proceedings and Abstracts of international conferences on the interdisciplinary field of crystallography.